Оборона Гостомельського та Васильківського аеродромів: спроба реконструкції подій - Харук, А. (Український історичний журнал, 2022)
Мета статті полягає у відтворенні ходу подій під час намагань росіян висадити
десанти на аеродромах у Василькові й Гостомелі. Методологія дослідження побудована на
застосуванні проблемно-хронологічного, а також методів аналізу та синтезу. Основні результати. Важливою ланкою плану повномасштабного вторгнення в Україну було проведення повітряно-десантних операцій у районі Києва. Російське командування розраховувало захопити
аеродроми поблизу столиці України, щоб забезпечити перекидання підкріплень авіацією.
Пріоритетною ціллю стали Гостомель і Васильків. Зусилля ворога своєї мети не досягли.
Повітряно-десантні війська Росії не змогли показати себе в діях за прямим призначенням,
і надалі у ході війни вони використовуватимуться як легкі механізовані з’єднання. The purpose of the article is to recreate the course of events in two combat episodes
of the Battle of Kyiv – the Russian side’s attempts to land at the airfields in Hostomel and
Vasylkiv and the resistance of Ukrainian troops to these attempts. The research methodology
is based on the application of the problem-chronological method, the method of analysis and
synthesis, the involvement of a wide range of sources. The main results. An important part
of Russia’s plan for a full-scale invasion of Ukraine was to conduct airborne operations in the
Kyiv area. The Russian command planned to seize the airfield near the Ukrainian capital to
ensure the transfer of reinforcements by air. The priority goal was Hostomel airfield. As a result
of the fighting on February 24–25, 2022, Russian troops managed to capture this airfield, but
its runway was destroyed by Ukrainian artillery fire. On the night of February 25–26, a Russian
landing party attempted to capture Vasylkiv airfield, but the attack was repulsed. In general, the
landing operations conducted by the Russians in the vicinity of Kyiv did not achieve their goal.
Hostomel airfield was captured only on the second day of the operation, by ground strike, but
the transfer of additional forces to Hostomel by air was impossible. The Russians did not manage
to get Vasylkiv airfield at all. Russian airborne troops were unable to show themselves in action
for their intended purpose. Later, during the war against Ukraine, they were used only as light
mechanized units. This use undermines the very meaning of the existence of airborne troops in
their Soviet/Russian form. On the other hand, the Ukrainian troops showed themselves quite well
in repelling the landing. A few units, moreover, are subordinated to various departments, although
they did not prevent, in the end, the capture of Hostomel by the enemy, but managed to make the
airfield unusable.